LEGAL ANALYSIS OF INTERFAITH MARRIAGE IN INDONESIA - Permanasari, Lolita (jfpublisher, 2023)
In Article 2 paragraph (1) of Marriage Law, it has been stated that the provisions and conditions for a valid marriage are marriages that are conducted according to the laws of each religion and belief. Interfaith marriage is a delicate religious topic that has a lot to do with someone spiritual views. Every religion in the world has its own laws governing marriage as a religious matter. The research method used is normative juridical research. This research used laws and regulations regarding to interfaith marriage, including Civil Code, Law number 1 of 1974 on Marriage, and Law No. 23/2006 on Population Administration. Based on research result, when associated with legal issues in the marriage that occurs, it can be interpreted that interfaith marriages can only be registered in civil registry, but it does not mean that it is religiously valid. Interfaith marriages are also associated with human rights, freedom in human rights to marry and build a family remains subject to the rules or Law Number 1 of 1974, this is clearly seen in the Human Rights Law in Indonesia Article 10 paragraphs (1) and (2) which state that this freedom must be in accordance with statutory regulations.